2007
DOI: 10.1016/j.febslet.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a bacterial albumin‐binding domain at 1.4 Å resolution

Abstract: The albumin-binding domain, or GA module, of the peptostreptococcal albumin-binding protein expressed in pathogenic strains of Finegoldia magna is believed to be responsible for the virulence and increased growth rate of these strains. Here we present the 1.4 Å crystal structure of this domain, and compare it with the crystal structure of the GA-albumin complex. An analysis of protein-protein interactions in the two crystals, and the presence of multimeric GA species in solution, indicate the GA module is ''st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…GA (protein G-like albumin binding module) is found in a family of surface proteins of different bacterial species. It has been reported that the GA module binds close to a cleft at a site in domain IIA and domain IIIB of the albumin molecule 20,21 and involves a single site consisting of a segment spanning residues 330-548 ( Fig. 2D).…”
Section: Bacterial Protein and Albumin Associationmentioning
confidence: 95%
“…GA (protein G-like albumin binding module) is found in a family of surface proteins of different bacterial species. It has been reported that the GA module binds close to a cleft at a site in domain IIA and domain IIIB of the albumin molecule 20,21 and involves a single site consisting of a segment spanning residues 330-548 ( Fig. 2D).…”
Section: Bacterial Protein and Albumin Associationmentioning
confidence: 95%
“…The ALB8 gene encoding the GA module was obtained as synthetic DNA in a carrier plasmid and was subcloned into a pET28 vector (Novagen) with an N-terminal histidine tag and thrombin protease cleavage site (HHHHSSGLVPRGSHM). The GA module was overexpressed and was then purified using an Ni 2+ -loaded chelating column and an imidazole gradient using standard procedures as described elsewhere (Cramer et al, 2007). Owing to the presence of heterogeneous cleavage products after thrombin digestion, the N-terminal tag was left intact for crystallization.…”
Section: Protein Purification Complex Formation and Crystallizationmentioning
confidence: 99%
“…This study demonstrated that the binding of G148-ABD to HSA can be abolished by only a few amino acid changes and the overall mapped binding region in G148-ABD is largely supported by NMR-perturbation studies performed on both the homologous ALB8-GA [26] and G148-ABD [4] and by the ALB8-GA:HSA structural complex [28]. However, the NMR-studies generally assign larger binding surfaces, which may in part be due to contacts between the albumin-binding domains, as indicated by the crystal structure of a dimer of ALB8-GA [27]. Neither NMR nor X-ray studies have specified the central importance of the second helix for binding as accurately as the mutational analysis of G148-ABD.…”
Section: Introductionmentioning
confidence: 99%